AOSspine masters series. - Vialle, Luiz Roberto; Fehlings, Michael; Weidner, Norbert (Thieme, 2017)
World-renowned experts share the latest updates in translational research as well as surgical and nonsurgical strategies for treating spinal cord injury Spinal cord injury (SCI) is a devastating, clinically challenging injury, leading to varying degrees of neurological function impairment and paralysis. Underlying biological mechanisms either inhibit or promote new growth in the spinal cord. Researchers have been making important discoveries about how neurons and their axons grow in the central nervous system and why they fail to regenerate after SCI. Although progress has been steady, there r.